A Magyar Királyi Honvédség gyorscsapatainak alkalmazása 1938-1941 - Kiss, Gábor Ferenc (Közép-Európai Közlemények, 2013)
In my article I would like to present the the operations of the Hungarian Mobile Forces (cavalry, mechanised infantry, bicycle infantry and armored units) between 1938–1941. These forces were the one of the most modern arm of the Royal Hungarian Defence Forces. This new branch of army was established in 1938 in paralel with the international trends. After the establisment these forces was used to occupy the southern parts of Felvidék. In 1939 Hungary was given an opportunity to get back Kárpátalja, what was the second deployment. This was the first occasion for the hungarian military forces to fight since the World War 1. The new year brought the occupation of northern Transylvania by military troops. The most notable deployment of the mobile forces came in 1941 in Délvidék. The Mobile Corps was the spearhead of the attacking hungarian 3rd Army.